PENGARUH BAURAN PEMASARAN 4P TERHADAP KEPUTUSAN PEMBELIAN RUMAH (STUDI KASUS KONSUMEN TJOKRO BOULEVARD BANTUL) - Sari, Erma Yunita; Prasojo, Eko (Journal Competency of Business, 2023)
This study aims to determine the effect of product, price, location and promotion on purchasing decisions, as measured by partial significance test (t test) and simultaneous significance test (F test), the data analysis technique used to answer hypothesis by multiple linear regression test. The population in this study is consumers / buyers of Tjokro Boulevard Bantul housing. The sampling technique uses the Axial Sampling method with a total sample of 50 people. The results of this study indicate that: 1) The product has a positive effect on purchasing decisions, this is evidenced by the significance of 0.000 < 0.05, the value of t-count (3.791) > t-table (1.676); Price has a positive effect on purchasing decisions, this is evidenced by the significance of 0.002 < 0.05, calculated t-value (3.297) > t-table (1.676); Location has a positive effect, this is evidenced by the significance of 0.000 < 0.05, the value of t-count (4.084) > t-table (1.676); Promotion has a positive effect on purchasing decisions, this is evidenced by a significance of 0.002 < 0.05, calculated t-value (3.374) > t-table (1.676). 2) Product, price, location, and promotion have an influence on purchasing decisions, this is evidenced by significance 0.000 < 0.05, calculated Fvalue (78.776) > Ftable (2.57). 3) Multiple linear equation Y = -2.414+ 0.334 (X 1)+0.247 (X 2) + 0.302 (X 3) + 0.228 (X 4). 4) The coefficient of determination (R2) is 0.864 indicating that product, price, location, and promotion have an influence on purchasing decisions by 86.4% while 13.6% is influenced by other factors not examined.